1969
DOI: 10.1111/j.1365-3091.1969.tb01119.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Clay Minerals in the Oceans

Abstract: SUMMARY In order to obtain data comparable to those of Biscaye (1965) on the Atlantic Ocean, the authors carried out quantitative X‐ray determinations of clay minerals in the sediments of the Indian and Pacific oceans using the Biscayemethod.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(58 citation statements)
references
References 7 publications
3
52
0
Order By: Relevance
“…Figure 2 shows the distribution of illite in North Pacific sediments finer than 2/xm, calculated according to Biscaye's (1965) method. The pattern is consistent with earlier maps by Griffin et al (1968) andRateev et al (1969), although it shows more detail because of the larger number of samples. The agreement between our numerical values and those of Griffin et al (1968) is an indication of the degree to which standardization of sample preparation and analytical techniques have allowed clay-mineral data from different laboratories to be merged.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Figure 2 shows the distribution of illite in North Pacific sediments finer than 2/xm, calculated according to Biscaye's (1965) method. The pattern is consistent with earlier maps by Griffin et al (1968) andRateev et al (1969), although it shows more detail because of the larger number of samples. The agreement between our numerical values and those of Griffin et al (1968) is an indication of the degree to which standardization of sample preparation and analytical techniques have allowed clay-mineral data from different laboratories to be merged.…”
Section: Resultssupporting
confidence: 81%
“…Over the past 15 years, a number of papers have described the distribution and abundance of clay minerals within major ocean basins (Biscaye, 1965;Gorbunova, 1963;Griffin and Goldberg, 1963;KoUa et al, 1976;Venkatarathnam and Biscaye, 1973;YeroshchevShak, 1962) and even the world ocean (Griffin et al, 1968;Rateev et al, 1969). In all cases, however, the abundance values were derived from the assumptions that peak-area ratios from X-ray powder diffractograms are related to the corresponding weight ratios of clay minerals by known simple factors (Biscaye, 1965;modified from Johns et al, 1954), and that clay minerals constitute 100% of the fine fraction of deep-sea sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Biscaye (1965), Griffin et al (1968), and Rateev et al (1969) has shown that the distribution of clay minerals in recent marine sediment is chiefly detrital and related to general source areas on adjacent continents. Diagenetic alteration does not provide a viable alternative explanation for the observed stratigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Their possible origins and their significance were considered in the light of works by several authors, in particular, that of Mason et al (1960), Millot (1964, YeroschevShak (1964), Biscaye (1965), Bonatti (1967), Griffin et al (1968), Rateev et al (1969), Paquet (1969), Tardy (1969), Trichet (1970), Chamley( 1971), Latouche (1971), and Jones et al (1971).…”
Section: General Outline Of the Mineralogy Of Depositsmentioning
confidence: 99%